2016
DOI: 10.1097/anc.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Among Parents of Newborn Infants

Abstract: BACKGROUND Health Literacy is the ability to obtain, process, and understand health information to make knowledgeable health decisions. PURPOSE To determine baseline health literacy of NICU parents at a tertiary care hospital during periods of crucial information exchange. METHODS Health Literacy of English speaking NICU parents was assessed using the Newest vital Sign (NVS) on admission (n=121) and discharge (n=59). A quasi-control group of well newborn (WBN) parents (n=24) and prenatal obstetric clinic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 18 publications
0
17
0
3
Order By: Relevance
“…When studying parents of infants hospitalized in the neonatal intensive care unit (NICU), Mackley, Winter, Guillen, Paul, and Locke (2016) found that during times of complex information exchange regarding the condition and care of their infants, one third of parents scored as having suspected limited health literacy. Furthermore, when assessing nurses’ subjective interpretations of parent understanding of complex information in discharge teaching, they perceived adequate comprehension by parents 83.3% of the time while 32% of parents exhibited suspected limited health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…When studying parents of infants hospitalized in the neonatal intensive care unit (NICU), Mackley, Winter, Guillen, Paul, and Locke (2016) found that during times of complex information exchange regarding the condition and care of their infants, one third of parents scored as having suspected limited health literacy. Furthermore, when assessing nurses’ subjective interpretations of parent understanding of complex information in discharge teaching, they perceived adequate comprehension by parents 83.3% of the time while 32% of parents exhibited suspected limited health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that 43% of NICU parents may have a low level of health literacy, which impacts their ability to understand, retain, and process health information. 18 In addition, many parents report high levels of stress while their infant is in the NICU, 19 which can also significantly impact their ability to retain what has been learned. 20 Standardized parent education programs have shown benefits to parents and infants while also creating efficiencies.…”
Section: Background and Significancementioning
confidence: 99%
“…A capacidade de os pais compreender e assimilar a informação é outro fator facilitador 7 . Essa capacidade é afetada pelo stresse associado ao internamento, pela quantidade de informação especializada que é transmitida 9 e pelo nível de Letramento em Saúde (LS) parental 10 . A informação pode, inclusive, tornar-se inútil quando não é transmitida atempadamente, não é monitorizada a compreensão ou quando os esclarecimentos são inconsistentes 6 .…”
Section: Introductionunclassified